The incidence and causes of hypercalcaemia. Issue 743 (September 1987) - Dent, D. M.; Miller, J. L.; Klaff, L.; Barron, J.
Abstract : A prospective screen for hypercalcaemia in 58, 053 hospital in-patients was conducted over 12 months. The incidence of hypercalcaemia was 0.6%, being transient in 19.2% of patients and sustained in the remainder. The most common causes in the sustained group were malignancy (45%) and primary hyperparathyroidism (16.5%). The incidence of primary hyperparathyroidism was 78/100, 000 hospital in-patients, and its discovery was directly attributable to the survey in over half the cases.